Pre-treatment anxiety in a dental hygiene recall population: a cross-sectional pilot study. Issue 1 (December 2016) - Hofer, Deborah; Thoma, Myriam; Schmidlin, Patrick; Attin, Thomas; Ehlert, Ulrike; Nater, Urs
Abstract Background Increased levels of anxiety may affect a patient's receptiveness to treatment, health care information and behaviour modification. This study was undertaken to assess pre-treatment anxiety in a dental hygiene recall population maintaining a schedule of regular preventive care appointments. Methods The sample population consisted of 46 consecutive adult recall patients waiting for their regularly scheduled dental hygiene appointment. Pre-treatment state (current) anxiety was assessed using the State-Trait-Anxiety Inventory (STAI), State form; dental anxiety with the Hierarchical Anxiety Questionnaire (HAQ); subjective stress using a visual analogue scale (VAS); and mood/alertness/calmness using the Multidimensional Mood Questionnaire (MDMQ). Results Two distinct groups, based on state anxiety scores, were formed; one displaying increased levels of pre-treatment anxiety (n  = 14), the other low anxiety (n  = 32). The HA group was characterized by significantly higher dental anxiety and subjective stress levels prior to treatment; as well as worse mood, lower alertness, and less calmness in the dental office setting. There was no correlation between anxiety level and years in dental hygiene recall. Conclusions A high level of pre-treatment anxiety was present in about one third of the sample population. The prevalence of this anxiety demonstrates the need for both early recognition and patient management strategies (psychological and pain management) to positively influence their treatment experience.